PENGARUH LOCUS OF CONTROL DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMKN 4 KLATEN DENGAN KEPUASAN KERJA SEBAGAI INTERVENING - Hesthi Ruscahyono (STIE AUB Surakarta, 2014)
The purpose of this study is to examine the effect of locus of control, work environment and job satisfaction on the performance of teachers at SMK 4 Klaten. Hypotheses that have been formulated in this study are: significant effect of locus of control and the work environment directly and indirectly through job satisfaction on the performance of teachers at SMK 4 Klaten. This study is a survey research. The data used are the primary data collected through the questionnaires to teachers of SMK Negeri 4 Klaten. The obtained data is tested with a test of validity, reliability testing, path analysis, t test, F test and test R2. T test results showed that the locus of control and the work environment significantly influence the performance of teachers at SMK 4 Klaten. In addition, the locus of control has a direct influence on the performance of 0.373 with a significance of 5%, so that the locus of control on the performance of teachers has the greatest influence than other variables. F test results show that the value of F = 8.425 with a significance of 0.000 < 0.05, so it can be concluded jointly independent variables, namely locus of control, work environment and satisfaction affect the performance of teachers at SMK 4 Klaten. Test results of total R2 is 0.827 meaning that the model with this equation, the independent variables (locus of control, work environment and job satisfaction) are able to explain the dependent variable (performance) of 82.7% and the remaining 17.3% is explained by other variables such as: leadership, motivation, organizational commitment, work discipline. The results of direct and indirect effects showed: 1) the direct effect of locus of control on the performance of teachers is greater than the indirect effect of locus of control on the performance of teachers through job satisfaction, so as to improve the performance of teachers is more effective through the direct pathway, 2) Effect of total locus of control to influence the performance of teachers is greater than the total effect of work environment on the performance of teachers, so as to improve teacher performance more effectively through increased locus of control. Keywords: locus of control, work environment, satisfaction, performance